CASPIAN BIOLOGICAL RESOURCES - M. K. Guseynov; K. M. Guseinov; A. Sh. Gasanova (Юг России: экология, развитие, 2015)
Aim. We present the data on the biological resources of the Caspian Sea, based on the analysis of numerous scientific sources published between years of 1965 and 2011. Due to changes in various biotic and abiotic factors we find it important to discuss the state of the major groups of aquatic biocenosis including algae, crayfish, shrimp, pontogammarus, fish and Caspian seal. Methods. Long-term data has been analyzed on the biology and ecology of the main commercial fish stocks and their projected catches for qualitative and quantitative composition, abundance and biomass of aquatic organisms that make up the food base for fish. Results and discussion. It has been found that the widespread commercial invertebrates in the Caspian Sea are still poorly studied; their stocks are not identified and not used commercially. There is a great concern about the current state of the main commercial fish stocks of the Caspian Sea. A critical challenge is to preserve the pool of biological resources and the restoration of commercial stocks of Caspian fish. For more information about the state of the marine ecosystem in modern conditions, expedition on Caspian Sea should be carried out to study the hydrochemical regime and fish stocks, assessment of sturgeon stocks, as well as the need to conduct sonar survey for sprat stocks. Conclusions. The main condition for preserving the ecosystem of the Caspian Sea and its unique biological resources is to develop and apply environmentally-friendly methods of oil, issuing concerted common fisheries rules in various regions of theCaspian Sea, strengthening of control for sturgeon by all Caspian littoral states. The basic principle of the protection of biological resources is their rational use, based on the preservation of optimal conditions of their natural or artificial reproduction.